Five weeks of sprint and high-intensity interval training improves paddling performance in adolescent surfers - Farley, O. R. L.; Secomb, J. L.; Parsonage, J. R.; Lundgren, L. E.; Abbiss, C. R.; Sheppard, J. M. (The Journal of Strength and Conditioning Research, 2016)
The purpose of our study was to examine the effects of sprint interval training (SIT; 10 seconds) and high-intensity interval training (HIT; 30 seconds) on surfing athletes paddling performance (400-m time trial and repeat-sprint paddle performance). Twenty-four competitive adolescent surfers (19 male, 5 female; age = 14.4 ± 1.3 years, mass: 50.1 ± 10.7 kg, and stature: 159.9 ± 10.3 cm) were assigned to perform either 5 weeks of SIT and HIT. Participants completed a repeated-sprint paddle ability test (RSPT, 15-m surfboard sprint paddle initiated every 40 seconds × 10 bouts) and 400-m endurance surfboard paddle time trial before and after training. High-intensity interval training decreased the total time to complete the 400 m by 15.8 ± 16.1 seconds (p = 0.03), and SIT decreased the total time to complete the RSPT by 6.5 ± 4.3 seconds (p = 0.02). Fatigue index during the RSPT (first—slowest effort) was lower after HIT and SIT (p = 0.001 and p = 0.02, respectively). There were no significant differences in performance changes in the 400 m (total time) and RSPT (total time, fastest 15 m time, and peak velocity) between HIT and SIT. Our study indicates that HIT and SIT may be implemented to the training program of surfers to improve aerobic and repeat-sprint paddle ability, both of which are identified as key aspects of the sport. In addition, these findings indicate that 400-m paddle and RSPT can discriminate between aerobic and anaerobic training adaptations, with aerobic gains likely from HIT and anaerobic gains from SIT.